A comprehensive bioinformatics analysis of pathways and biomarkers shared between type 2 diabetes mellitus and chronic obstructive pulmonary disease - Hu, Tingting; Duan, Xiaomei; Gao, Jiale; Li, Zheng; Xu, Dan; Jing, Jing; Li, Fengsen; Ding, Jianbing; Ma, Li; Jiang, Min; Wang, Jing (Frontiers in Immunology, 2025)
BackgroundT2DM and COPD are prevalent and high-burden diseases which are closely related, with poor patient outcomes. In this study, we aimed to identify common diagnostic markers for T2DM and COPD and their therapeutic potential.MethodsMicroarray data from the GEO database were analyzed to identify DEGs, whereas WGCNA, co-differential gene analyses were employed to identify co-expression modules and DEGs functions. Diagnostic markers were determined through machine learning and validated with human blood PBMC and single-cell sequencing.ResultsA total of 738 and 1391 DEGs were identified for T2DM and COPD, respectively. Among these, 25 key genes and 75 co-differential genes were recognized, predominantly enriched in immune-related pathways, particularly those involving T-cell signaling. Eight diagnostic markers were identified through machine learning approaches. Subsequent validation using human PBMC from three groups (Ctrl, COPD, and T2DM, n=15 each) confirmed PES1 (AUC 0.676 and 0.615), CANX (AUC 0.668 and 0.642), SUMF2 (AUC 0.684 and 0.679), and DCXR (0.625 and 0.606) as shared diagnostic markers. Analysis of single-cell sequencing data from blood and bone marrow and RT-qPCR results from healthy individuals and patients with T2DM combined with COPD showed that only SUMF2 showed a statistically significant difference in expression levels in comorbid patients and was strongly associated with T-cell subpopulations.ConclusionThe T-cell pathway may be involved in the pathogenesis of T2DM and COPD, and SUMF2 may be a potential diagnostic marker, and its high expression in T-cell subsets suggests a possible role in the immunomodulatory mechanisms underlying the two diseases.